1990
DOI: 10.1038/347092a0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV replication by pokeweed antiviral protein targeted to CD4+ cells by monoclonal antibodies

Abstract: Functional impairment and selective depletion of CD4+ T cells, the hallmark of AIDS, are at least partly caused by human immunodeficiency virus (HIV-1) type 1 binding to the CD4 molecule and infecting CD4+ cells. It may, therefore, be of therapeutic value to target an antiviral agent to CD4+ cells to prevent infection and to inhibit HIV-1 production in patients' CD4+ cells which contain proviral DNA. We report here that HIV-1 replication in normal primary CD4+ T cells can be inhibited by pokeweed antiviral pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
117
0
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(121 citation statements)
references
References 32 publications
1
117
0
3
Order By: Relevance
“…Since its initial description as an antiviral agent against tobacco mosaic virus (1), PAP has been demonstrated to reduce the propagation of several plant and animal viruses, including potato virus X, HIV, and influenza (2)(3)(4). It therefore holds promise as a broad-spectrum antiviral agent.…”
Section: Pokeweed Antiviral Protein (Pap)mentioning
confidence: 99%
“…Since its initial description as an antiviral agent against tobacco mosaic virus (1), PAP has been demonstrated to reduce the propagation of several plant and animal viruses, including potato virus X, HIV, and influenza (2)(3)(4). It therefore holds promise as a broad-spectrum antiviral agent.…”
Section: Pokeweed Antiviral Protein (Pap)mentioning
confidence: 99%
“…Studies that compare the relative antiviral properties of a number of RIPs showed that all of the RIPs tested had antiviral activity, but none was as effective as PAP (4). PAP has been shown to inhibit infection of both Vero and HeLa cells by herpes simplex virus (5) and to inhibit human immunodeficiency virus 1 (HIV-1) replication in T cells and macrophages infected in vitro at concentrations that do not inhibit cellular protein synthesis (6). A number of recent studies have shown that conjugating PAP with monoclonal antibodies dramatically increases its potency against cells infected with HIV and human cytomegalovirus (7).…”
mentioning
confidence: 99%
“…That targeted toxins represent a rational approach to cytocidal therapy in certain infectious diseases, envisaged earlier, has indeed been attested to, by the success of anti CD4-toxin and CD4-toxin conjugates for combating human immunodeficiency virus [12,13]. Moreover, such hybrid molecules prepared by chemical conjugation, linked to either antireceptor antibodies or ligands, have been demonstrated to selectively kill cells, displaying the complementary determinants (antigen or receptor) on their surfaces [14].…”
mentioning
confidence: 99%